Assessing audience response systems using task-technology fit - Mantikayan, Jonathan Mamangkiang; Ayu, Media Anugerah (2013)
An Audience Response Systems (ARS) is a tool to increase active learning and gather immediate feedback from the audience in real time. This tool is used in a classroom environment to support teaching and learning. The aim of this paper is to explore the perceptions on the leading pedagogy and practices for using ARS technology in the classroom. In order for an information technology to have a positive impact, the technology must be utilized and must be a good fit with the tasks it supports. This study also highlights the importance of the fit between technology and users’ task. The sample learning institution is Adni International Islamic School. This research used survey method to determine the perceived fit of ARS in secondary computer studies class. The Task- Technology Fit (TTF) theoretical model was used to assess ARS technology. The findings from the study suggest that the system positively impacts the students. As a result, the students believed that ARS have high perceived fit in the classroom.